Southern food studies: An overview of debates in the field - Cooley, Angela Jill (History compass, 2018)
Southern food studies is a young interdisciplinary field originating in the 1970s and 1980s. Today, it is a vibrant area of research that includes scholars, journalists, food writers, documentarians, activists, and chefs. Much of the literature revolves around the ways in which southern food provides a lens for understanding southern culture and identity. Some southern studies scholars, however, challenge this approach and argue that the literature of southern food is too nostalgic, ahistorical, and based on outdated theoretical understandings of the American South. This debate suggests a possible foundational change in the way we understand the field.